DAMPAK BERKEMBANGNYA OBJEK WISATA DI KAWASAN DANAU PLTA (Pembangkit Listrik Tenaga Air) KOTO PANJANG TERHADAP SOSIAL EKONOMI MASYARAKAT DESA PULAU GADANG, KECAMATAN XIII KOTO KAMPAR, KABUPATEN KAMPAR - Norvi Rutari; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted in the Tourism Object on Lake Area Koto Panjang, Pulau Gadang Village. Focus in this research are increase the businesses and incomes. More over, the impact of the development of tourism object on the social economic. The method was use quantitative which describes the phenomena social economis regarding tourism obyek. The data collection technique of this research were survey, questionnaire, observation and documentation. The results of this research shows the habit of the community as tourism objects increased as a destination crowded by local and outside District. This situation change the social values which was felt by the community, since many visitors coming. The impact give the opportunities for local people who to developped bussiness.Keywords: Tourism Object, Social Economic Impact